The Influence of Local Taxes and Regional Retributions on Local Own-Source Revenue in East Nusa Tenggara Province, Indonesia - Luan, Kristina Yanuaria M; Dewi, Siti Ratna Sari (Golden Ratio of Data in Summary, 2026)
This study examines the influence of local taxes and regional retributions on the optimization of local own-source revenue in East Nusa Tenggara Province. Using a quantitative approach with panel data regression, the research analyzes fiscal performance across regencies and municipalities during 2019–2023. The results reveal that local taxes have a significant positive impact on strengthening regional fiscal capacity, while regional retributions also contribute positively, although with less consistency due to administrative and collection challenges. These findings emphasize the crucial role of transparent tax governance, efficient collection systems, and equitable fiscal policies in enhancing financial independence at the local level. Theoretically, this study reinforces regional autonomy and development-from-below perspectives, highlighting how local fiscal instruments drive sustainable regional development. Practically, the study provides insights for policymakers to improve tax administration and optimize retribution potential. However, the research is limited to fiscal variables and secondary data; future studies are encouraged to incorporate governance, institutional, and socio-economic factors to provide a more comprehensive understanding of regional revenue optimization.